Tau phosphorylation sites serine202 and serine396 are differently altered in chronic traumatic encephalopathy and Alzheimer's disease. Issue 8 (2nd December 2021) - Stathas, SpiroAnthony; Alvarez, Victor E.; Xia, Weiming; Nicks, Raymond; Meng, Gaoyuan; Daley, Sarah; Pothast, Morgan; Shah, Arsal; Kelley, Hunter; Esnault, Camille; McCormack, Robert; Dixon, Erin; et al.
Abstract: Introduction: Chronic traumatic encephalopathy (CTE) is a neurodegenerative tauopathy associated with repetitive head impacts (RHI) typically sustained by contact sport athletes. Post‐translation modifications to tau in CTE have not been well delineated or compared to Alzheimer's disease (AD). Methods: We measured phosphorylated tau epitopes within dorsolateral frontal cortex from post mortem brains with neither CTE nor AD (n = 108), CTE (n = 109), AD (n = 223), and both CTE and AD (n = 33). Results: Levels of hyperphosphorylated tau (p‐tau)202, p‐tau231, and p‐tau396 were significantly increased in CTE. Total years of RHI exposure was significantly associated with increased p‐tau202 levels ( P = .001), but not p‐tau396 . Instead, p‐tau396 was most closely related to amyloid beta (Aβ)1‐42 levels ( P < .001). The p‐tau202 :p‐tau396 ratio was significantly increased in early and late CTE compared to AD. Discussion: In frontal cortex, p‐tau202 is the most upregulated p‐tau species in CTE, while p‐tau396 is most increased in AD. p‐tau202 and p‐tau396 measurements may aid in developing biomarkers for disease.